2022
DOI: 10.3389/fphys.2022.837631
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Bone Marker and Endocrine Responses to Resistance Exercise With and Without Blood Flow Restriction in Young Men

Abstract: In this study, we compared acute and chronic bone marker and hormone responses to 6 weeks of low intensity (20% 1RM) blood flow restriction (BFR20) resistance training to high intensity (70% 1RM) traditional resistance training (TR70) and moderate intensity (45% 1RM) traditional resistance training (TR45) in young men (18–35 years). Participants were randomized to one of the training groups or to a control group (CON). The following training programs were performed 3 days per week for 6 weeks for knee extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…A total of seven studies evaluated acute IGF-1 secretion at initial (n = 6), intermediate (n = 3), and late (n = 3) timepoints post-exercise. 35,45,46,70,75,77,79 There was no significant difference in IGF-1 plasma levels at the initial (SMD = 0.61 [95% CI −0.43, 1.65]) and intermediate (SMD = 0.34 [95% CI −0.41, 1.09]) post-exercise phases when comparing LL-BFRRE to overall FFRE. When performing subgroup analysis based on loading intensities, there was a borderline significant increase in IGF-1 plasma levels at the initial (SMD = 1.14 [95% CI −0.15, 2.42]) and intermediate (SMD = 0.88 [95% CI −0.14, 1.91]) post-exercise timepoints in LL-BFRRE compared to LL-FFRE.…”
Section: Hormonal Responses To Ll-bfrrementioning
confidence: 93%
See 3 more Smart Citations
“…A total of seven studies evaluated acute IGF-1 secretion at initial (n = 6), intermediate (n = 3), and late (n = 3) timepoints post-exercise. 35,45,46,70,75,77,79 There was no significant difference in IGF-1 plasma levels at the initial (SMD = 0.61 [95% CI −0.43, 1.65]) and intermediate (SMD = 0.34 [95% CI −0.41, 1.09]) post-exercise phases when comparing LL-BFRRE to overall FFRE. When performing subgroup analysis based on loading intensities, there was a borderline significant increase in IGF-1 plasma levels at the initial (SMD = 1.14 [95% CI −0.15, 2.42]) and intermediate (SMD = 0.88 [95% CI −0.14, 1.91]) post-exercise timepoints in LL-BFRRE compared to LL-FFRE.…”
Section: Hormonal Responses To Ll-bfrrementioning
confidence: 93%
“…Nine studies measured acute testosterone responses following LL-BFRRE compared to FFRE in the initial (n = 7), intermediate (n = 6), and late (n = 4) post-exercise time intervals. 35,[44][45][46]70,71,74,76,78 No differences in testosterone plasma levels were observed in the initial (SMD = 0.35 [95% CI −0.34, 1.05]) and intermediate (SMD = 0.55 [95% CI −0.26, 1.36]) post-exercise phase when comparing LL-BFRRE to overall FFRE. Subgroup analysis on load intensity did not demonstrate any difference at the initial and intermediate post-exercise time intervals between LL-BFRRE and LL-FFRE or HL-FFRE, respectively.…”
Section: Hormonal Responses To Ll-bfrrementioning
confidence: 99%
See 2 more Smart Citations
“…As well, blood flow restriction combined with endurance training has also been shown to improve cardiopulmonary health ( Conceição and Ugrinowitsch, 2019 ). Furthermore, BFRT can effectively improve muscle mass and strength in different populations ( Davids et al, 2021 ; Korkmaz et al, 2022 ), improve muscle fitness ( Hill et al, 2021 ), increase aerobic capacity ( Billaut et al, 2022 ), promote knee rehabilitation ( Centner et al, 2019 ), stimulate acute bone formation markers and hormonal responses ( Bemben et al, 2022 ), and improve athletic performance thereby maintaining overall good health ( Wortman et al, 2021 ). However, in the field of BFRT intervention for overweight/obesity, studies on anthropometric indicators and blood lipids have shown different results ( Da Silva et al, 2020 ; Kim and LeeDongminWon, 2021 ; Mohammadiyan et al, 2021 ; Yong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%